A Novel Mutation of SMAD3 Identified in a Chinese Family with Aneurysms-Osteoarthritis Syndrome. (29th June 2015) - Zhang, Wenwen; Zhou, Min; Liu, Cheng; Liu, Chen; Qiao, Tong; Huang, Dian; Ran, Feng; Wang, Wei; Liu, Changjian; Liu, Zhao
Abstract : Aneurysms-osteoarthritis syndrome (AOS) is a recently delineated autosomal dominant disorder characterized by aneurysms, dissections, and tortuosity throughout the arterial tree in association with early onset osteoarthritis, mild craniofacial features, and skeletal and cutaneous anomalies. Previous studies have demonstrated that mutations in SMAD3, a key regulator of TGF- β signal transduction, contribute to AOS. Here, we investigated a family of three generations affected by AOS. A novel SMAD3 mutation, c.266G>A (p.C89Y), was identified and cosegregated with the affected individuals in this family. Our finding expands the mutation spectrum of SMAD3 gene and further strengthens the connection between the presence of aneurysms-osteoarthritis phenotype and SMAD3 mutations, which facilitates the understanding of the genotype-phenotype correlation of AOS.